2011
DOI: 10.1016/j.combustflame.2010.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxy chemistry in the high-pressure ignition of n-butanol – Experiments and detailed kinetic modelling

Abstract: Due to its considerable advantages over lower alcohols such as ethanol, in particular with regard to its physical properties like volatility, corrosivity, and hygroscopicity, butanol has attracted considerable interest as a potential biofuel candidate. It has therefore been a target of a series of experimental studies probing its combustion characteristics. Nevertheless, its ignition behaviour at elevated pressures still remains widely unexplored. The present study investigates the oxidation of n-butanol at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 88 publications
5
98
3
1
Order By: Relevance
“…Nevertheless, the chemistry of the hydroxybutylperoxy species is important in the combustion of the other isomers of butanol as well. Using the high pressure shock tube at RWTH Aachen University, Vranckx et al 26 showed the importance of peroxy chemistry pathways in the autoignition of n-butanol. By adding a lumped peroxy model to an existing kinetic model for n-butanol combustion, they were able to substantially improve agreement of the model with their experiments at high pressure and low temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the chemistry of the hydroxybutylperoxy species is important in the combustion of the other isomers of butanol as well. Using the high pressure shock tube at RWTH Aachen University, Vranckx et al 26 showed the importance of peroxy chemistry pathways in the autoignition of n-butanol. By adding a lumped peroxy model to an existing kinetic model for n-butanol combustion, they were able to substantially improve agreement of the model with their experiments at high pressure and low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of ignition delay of the butanol isomers have been conducted in both apparatuses, including work in shock tubes by Black et al, 21 Heufer et al, 22 Moss et al, 23 Noorani et al, 24 Stranic et al, 17 Vasu et al, 25 and Vranckx et al, 26 and work in RCMs by Karwat et al 27 and Weber et al 16 These studies have covered a wide range of temperature-pressure regimes for n-butanol, from 1-90 bar and 675-1800 K. However, only the shock tube studies from Moss et al 23 and Stranic et al 17 have studied all four isomers of butanol, over the more limited range of 1-48 atm and 1022-1825 K.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies focusing on the combustion characteristics of butyl alcohols have also been published by presenting a wealth of combustion data obtained in shock-tubes [2,[13][14][15][16], flow reactors [17,18], jet-stirred reactors [2,[19][20][21][22][23] and flames [17,22,[24][25][26][27][28]. Coupled to these experiments, kinetic modeling studies have been performed, which resulted in a detailed description of the high-temperature fuel chemistry [2,13,17,19,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Combustion of the butanol isomers has been studied extensively in shock tubes [14][15][16][17][18][19][20][21][22][23][24]. This greatly contributed to the development of many chemical kinetic models [9,18,22,[24][25][26][27][28][29]. These chemical kinetic models provide a detailed description of the fuel ignition characteristics and hence a better understanding of the fuel/engine interactions through engine-combustion simulations.…”
Section: Introductionmentioning
confidence: 98%